Influence of Cognitive Errors on Investor’s Decısıon Makıng ın Nıgerıa: Array - Bankole, Oluwaseun Emmanuel (The Journal of Accounting and Management, 2020)
The study assessed the degree of influence of cognitive errors on investor’s decision making. The study used primary data. The population consisted of clients of the top 10 stockbroking firms registered by the Nigerian Stock Exchange as at 31st January, 2017. These 10 firms were selected because they constituted 68.72% of total value of transactions as at 31st January, 2017. Data on assessment of behavioural finance in investment decision making among investors in Nigeria were obtained through structured questionnaire which was administered to 30 clients of each stockbroking firm, totalling 300. The data were analysed using percentage and binary logistic regression. The study concluded that cognitive errors, proxied by representative bias, anchoring and adjustment bias , illusion of control bias, hindsight bias, framing bias and gamblers fallacy, significantly influenced investor’s decision making in Nigeria.